2022
DOI: 10.1038/s41418-022-00972-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ATP synthase c-subunit leak channel triggers cell death upon loss of its F1 subcomplex

Abstract: Mitochondrial ATP synthase is vital not only for cellular energy production but also for energy dissipation and cell death. ATP synthase c-ring was suggested to house the leak channel of mitochondrial permeability transition (mPT), which activates during excitotoxic ischemic insult. In this present study, we purified human c-ring from both eukaryotic and prokaryotic hosts to biophysically characterize its channel activity. We show that purified c-ring forms a large multi-conductance, voltage-gated ion channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 66 publications
4
35
0
Order By: Relevance
“…3, Datasets_S01-S07) and, in accordance with recent observations, reduced the F-ATP synthase stability and/or in gel activity after separation (Fig. 1) [44,45], it, however, drastically inhibited the channel activity of eluted F-ATP synthase (Fig. 2).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…3, Datasets_S01-S07) and, in accordance with recent observations, reduced the F-ATP synthase stability and/or in gel activity after separation (Fig. 1) [44,45], it, however, drastically inhibited the channel activity of eluted F-ATP synthase (Fig. 2).…”
Section: Discussionsupporting
confidence: 89%
“…4). (Separation of membrane-immersed subcomplex from the matrix-oriented soluble subcomplex during the PTP opening was confirmed in recent works [44,45].) If this assumption is correct, the molecular mass of the PTP complex should be at least 270-300 kDa and hardly exceed 500 kDa.…”
Section: Discussionmentioning
confidence: 79%
“…The mPTP is generally thought to be a large conductance channel (on the order of 1 nS) with multiple subconductance states [ 21 ]. However, it is also possible that the smaller and larger conductances represent separate physical processes, as suggested recently [ 22 ]. Previous studies have suggested that fA currents are sufficient to depolarize mitochondria [ 23 ].…”
Section: Discussionmentioning
confidence: 95%
“…Compelling evidence from several independent laboratories supports competing interpretations suggesting that a core part of PTP involves either the ATP synthase complex or ANT, both of which could be transformed into the high-conductance pore. 5 , 11 , 14 , 15 , 16 , 35 In both cell types lacking either ATPase or ANT, calcium treatment causes calcium release and membrane depolarization that is inhibited by CSA. 6 , 8 Here, using the same knockout cell models, we observed the phenomena of membrane depolarization.…”
Section: Discussionmentioning
confidence: 99%